MODEL PERAWATAN KESEHATAN KESELAMATAN KERJA BERBASIS AGRICULTURAL NURSING: STUDI ANALISIS MASALAH KESEHATAN PETANI - Susanto, Tantut; Purwandari, Retno; Wuryaningsih, Emi Wuri (Universitas Airlangga, 2016)
Introduction:The majority of Indonesian labor force at rural area works in the agricultural sector that risk for health problems related to the interaction of farmer and environment. It is necessary to approach health care safety based on primary health care for to prevent and reduce the risks of accidents or illness. This study identifies farmerâs health problem and their factors for developing occupational health nursing model-based agricultural nursing at rural area of Jember.Methods: A cross-sectional study of 169 farmers was done to investigate sociodemographic, lifestyles, environment of living and worked, health status and health problem. Data collected by the self-administered the questionnaire, physical assessment, and blood test. The descriptive and comparative analyses include chi-square tests and logistic and multinomial regression analyses were used to assess the relationships between factors to the presence of health problems. Results: There was differences between sociodemographic, environment of living and worked and the health problems of farmers (p<0.05). Almost 37.9% of farmers is an illness. Among 28.5% of underweight and 9.5% of overweight that related to age, drink of coffee, and excess day of work. 62.6% of anemia that related to gender and smoking habit. Meanwhile, 45.2% of systolic hypertension and 35.8% diastolic hypertension that caused by worked of overload. Furthermore, 50.3% of pain on joint and bone related to age and recess of worked.Discussion: The health problems of farmers were characterized by the nutritional problem, anemia, hypertension, and pain that related to the sociodemographic environment of biologic, psychologic, and worked. An agricultural nursing model could be developed for assessment of related factors that formulated diagnoses of health problems on farmers at rural area.Â Introduction:The majority of Indonesian labor force at rural area works in the agricultural sector that risk for health problems related to interaction of farmer and environment. It is necessary to approach health care safety based on primary health care for to prevent and reduce the risks of accidents or illness. This study identifies farmerâs health problem and their factors for developing occupational health nursing model-based agricultural nursing at rural area of Jember.Methods: A cross-sectional study of 169 farmers was done to investigate sociodemographic, lifestyles, environment of living and worked, health status and health problem. Data collected by the self administered questionnaire, physical assessment, and blood test. The descriptive and comparative analyses include chi-square tests and ogistic and multinomial regression analyses were used to assess the relationships between factors to the presence of health problems. Results: There was differences between sociodemographic, environment of living and worked and the health problems of farmers (p<0.05). Almost 37.9% of farmers is illness. Among 28.5% of underweight and 9.5% of overweight that related to age, drink of coffe, and excess day of work. 62.6% of anemia that related to gender and smoking habit. Meanwhile, 45.2% of sistolic hypertension and 35.8% diastolic hypertension that caused by worked of overload. Furthermore, 50.3% of pain on join and bone related to age and recess of worked. Discussion: The health problems of farmers was characterized of nutritional problem, anemia, hypertension, and pain that related to sociodemographic environment of biologic, psychologic, and worked. Agricultural nursing model could be develop for assessesment of related factors that formulated diagnoses of health problems on farmers at rural area.Â